Identification of the Immunological Changes Appearing in the CSF During the Early Immunosenescence Process Occurring in Multiple Sclerosis - Picón, Carmen; Tejeda-Velarde, Amalia; Fernández-Velasco, José Ignacio; Comabella, Manuel; Álvarez-Lafuente, Roberto; Quintana, Ester; Sainz de la Maza, Susana; Monreal, Enric; Villarrubia, Noelia; Álvarez-Cermeño, José Carlos; Domínguez-Mozo, María Inmaculada; Ramió-Torrentà, Lluís; et al. (Frontiers in Immunology, 2021)
Aging induces changes in the immune response in multiple sclerosis (MS), which influence the treatment response and increase the risk of infections. We explored whether lipid-specific oligoclonal IgM bands (LS-OCMB) associated with highly inflammatory MS modify the immunological profile induced by age in MS. This cross-sectional study included 263 MS patients who were classified according to the presence (M+, n=72) and absence (M-, n=191) of LS-OCMB. CSF cellular subsets and molecules implicated in immunosenescence were explored. In M- patients, aging induced remarkable decreases in absolute CSF counts of CD4+ and CD8+ T lymphocytes, including Th1 and Th17 cells, and of B cells, including those secreting TNF-alpha. It also increased serum anti-CMV IgG antibody titers (indicative of immunosenescence) and CSF CHI3L1 levels (related to astrocyte activation). In contrast, M+ patients showed an age-associated increase of TIM-3 (a biomarker of T cell exhaustion) and increased values of CHI3L1, independently of age. Finally, in both groups, age induced an increase in CSF levels of PD-L1 (an inductor of T cell tolerance) and activin A (part of the senescence-associated secretome and related to inflammaging). All these changes were independent of the disease duration. Finally, this resulted in augmented disability. In summary, with age, all MS patients experience a modest induction of T-cell tolerance and a clear activation of the innate immunity, resulting in increased disability. Additionally, M- patients show clear decreases in CSF lymphocyte numbers, which could increase the risk of infections. Thus, age and immunological status are important for tailoring effective therapies in MS.